Αριθμητική Διερεύνηση:Γεφύρας υποβαλόμενης σε τεκτονική διάρρηξη - Κλάδης, Αντώνιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών, 2016)
Surface fault ruptures may inflict serious damage to bridges built on or near them. In the three notorious earthquakes of Kocaeli, Chi – Chi and Wenchuan a number of bridges were crossed by the emerging normal and thrust faults suffering significant damage, demonstrating, at the same time, the need to account for tectonic deformation in seismic design. Previous research efforts on the subject had been focused on the investigation of the decomposed problem, in which the free-field solution of the fault propagation is preceding the analysis of the bridge system (subjected to the calculated deformations of the free-field step). This paper, attempts a robust investigation of the entire bridge system (soil foundation, pier and deck) with the intention to elucidate the significance (or not) of the kinematic constraints imposed by the superstructure on the overall bridge response. To this end, a typical high-way bridge founded on surface footing is subjected to a dip – slip (normal and thrust) faulting. A series of 1-g physical model experiments are conducted in the split-box of the Soil Mechanics Laboratory of the National Technical University of Athens. In this first part of study, Class-A numerical prediction of forthcoming experimental results is attempted, validating simultaneously the decoupled methodology by Anastasopoulos et al. 2008. 2D finite element analyses accounting for soil strain-softening are conducted. The position of the footing relative to the surface fault rupture and the imposed kinematic constraints on the abutments of bridge are also parametrically investigated, assessing the various mechanisms develop and the corresponding stress on bridge.